2007
DOI: 10.1093/molbev/msm123
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Inefficient Selection Against Deleterious Mutations in Cytochrome Oxidase I of Asexual Bdelloid Rotifers

Abstract: Evolutionary theory predicts that natural selection should be less efficient in asexually than in sexually reproducing organisms. Obligate asexuals are expected to adapt slowly to changing environments and to accumulate mildly deleterious mutations to their genomes, potentially explaining their typically short evolutionary lifespans. One group of animals that appear to challenge these ideas is the bdelloid rotifers, a large and ancient clade of obligate asexuals. Previous work has found no evidence for ineffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
62
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 55 publications
3
62
2
Order By: Relevance
“…Despite the fact that asexual reproduction facilitates clonal dispersion and renewal, it depends on mitotic divisions, which may increase the accumulation of somatic mutations, the Muller ratchet phenomena. Different studies with asexual species already revealed accumulation of somatic mutations on nonsynonymus position in clonal lineages compared with their nonclonal sibling species (Paland and Lynch, 2006;Barraclough et al, 2007). Unfortunately, the negative effects of deleterious mutations in wild populations of clonal species have never been fully investigated or proved, and these effects have been only supposed, but asexual lineages persist over short evolutionary periods (Schwander and Crespi, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that asexual reproduction facilitates clonal dispersion and renewal, it depends on mitotic divisions, which may increase the accumulation of somatic mutations, the Muller ratchet phenomena. Different studies with asexual species already revealed accumulation of somatic mutations on nonsynonymus position in clonal lineages compared with their nonclonal sibling species (Paland and Lynch, 2006;Barraclough et al, 2007). Unfortunately, the negative effects of deleterious mutations in wild populations of clonal species have never been fully investigated or proved, and these effects have been only supposed, but asexual lineages persist over short evolutionary periods (Schwander and Crespi, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using population genetic data shows, however, that the effectiveness of selection on codon usage is greatly reduced in two different selfing species of plants compared with their outcrossing relatives (Qiu et al 2011). Similarly, the efficacy of selection on nonsynonymous mutations is higher in the outcrossing plant Capsella grandiflora than in the related selfer A. thaliana (Slotte et al 2010); in outcrossing vs. selfing species of Neurospora (Nygren et al 2011); and in sexual vs. asexual lineages of Daphnia (Paland and Lynch 2006), freshwater snails (Johnson and Howard 2007), and rotifers (Barraclough et al 2007). We are, however, far from having a comprehensive picture of the consequences of evolving low or zero rates of recombination throughout the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas older studies indicated that bdelloids have not accumulated slightly deleterious 54 mutations faster than facultative sexual monogonont rotifers (Welch and Meselson, 2001;55 Birky et al, 2005), two newer studies using more elaborate and extensive sampling strategies 56 indicated the possible existence of this effect (Barraclough et al, 2007;Swanstrom et al, 57 2011). However, the results of these latter studies, which examine the rate of historical 58 accumulation of deleterious mutations, are complicated by several confounding factors.…”
mentioning
confidence: 99%
“…For 59 instance, the latest study showed no increased accumulation in bdelloid rotifers when 60 comparisons were made between monogononts and bdelloids from the same habitat 61 (Swanstrom et al, 2011). Additional potential confounding factors include methodological 62 aspects (e.g., sample-size effects (Swanstrom et al, 2011)), the long divergence time 63 separating bdelloids and monogononts (Barraclough et al, 2007), natural factors (e.g., 64…”
mentioning
confidence: 99%
See 1 more Smart Citation